WOMEN: THE PRESERVERS OF TRADITIONAL MEDICINE - P.G.LATHA AND S.RAJASEKHARAN
Medicinal plants form the largest segment of the biodiversity used by indigenous people. Traditionally, women are the providers of health care within the home. An important area of woman's involvement in traditional medicine is in the area of antenatal and post-natal centre. Besides, they handle specialized areas like bone setting, eye disease management etc. Food and nutrition are important areas of women's knowledge. Women also serve as conservers and cultivators of medicinal plants throughout the world. Education of women is important to create awareness of their rights and health care options. Women are thus the healers of human suffering in much of the world.